Effect of beam wobbling on laser welding of aluminum and magnesium alloy with nickel interlayer. (January 2019) - Shah, L.H.; Khodabakhshi, F.; Gerlich, A.
Graphical abstract: Highlights: Laser wobbling samples show better integrity due to the Mg-rich ductile interface. Laser beam wobble further enhances joint quality by widening the bond area. EDS data show interaction between Al and Ni elements to form Alx Niy compounds. Abstract: The influence of conventional laser keyhole welding and beam wobbling was evaluated at two weld travel speeds and power settings. Fracture in linear lap welds would occur during specimen preparation due to the presence of Al-rich brittle fusion zone, unless one utilizes a circular laser wobbling path (at 1000 Hz). Wobbling provided better integrity due to the presence of a Mg-rich ductile fusion zone and a larger bonded width. It can be concluded that laser beam wobbling enhances joint quality by widening the joint area and mitigating formation of brittle secondary phases at the joint fusion zone.